IMPACT OF ORAL REHABILITATION ON THE QUALITY OF LIFE OF PATIENTS WITH PSYCHIATRIC CONDITIONS AND MEDICATION MANAGEMENT - Kamel Earar; Gabi Topor; Norina Consuela Forna; Patru Radu Stanciu; Roxana Dragan; Alina-Ramona Dimofte; Marius Vacaru Carnaru; Iulian Catalin Bratu; Ionuta Grigore; Iulia Alecsandra Salcianu (Romanian Society of Oral Rehabilitation, 2024)
Psychiatric conditions significantly affect patients' quality of life, and associated dental problems can aggravate this situation. Through treatments such as dentures, dental implants, and periodontal therapies, oral rehabilitation plays a crucial role in relieving oral discomfort and improving masticatory function and aesthetics. This leads to increased self-confidence and reduced social stigma, which are essential for mental well-being. Also, improved oral health facilitates adherence to psychiatric drug treatments, preventing dental problems and stabilizing mental state. Integrating dental care into psychiatric treatment plans ensures a holistic approach, benefiting patients with optimal oral health and a better overall quality of life. This collaboration between healthcare professionals can reduce costs associated with re-hospitalizations and complications due to oral health neglect, highlighting the need for an integrative approach in the treatment of patients with psychiatric conditions.